Are People Living Near Modern Swine Production Facilities at Increased Risk of Influenza Virus Infection?. (7th December 2016) - Lantos, Paul M.; Hoffman, Kate; Höhle, Michael; Anderson, Benjamin; Gray, Gregory C.
Abstract : A spatiotemporal analysis revealed that during the 2009–2010 and 2010–2011 influenza seasons, influenza-like illnesses peaked earlier in counties with a large number of swine feeding operations. Abstract : Background: Swine can harbor influenza viruses that are pathogenic to humans. Previous studies support an increased risk of human influenza cases among individuals with swine contact. North Carolina has the second-largest swine industry in the United States. Methods: We investigated the spatiotemporal association between influenza-like illnesses (ILIs) and licensed swine operations from 2008 to 2012 in North Carolina. We determined the week in which ILI cases peaked and statistically estimated their week of onset. This was performed for all 100 North Carolina counties for 4 consecutive influenza seasons. We used linear models to correlate the number of permitted swine operations per county with the weeks of onset and peak ILI activity. Results: We found that during the 2009–2010 and 2010–2011 influenza seasons, both seasons in which the pandemic 2009 H1N1 influenza A virus circulated, ILI peaked earlier in counties with a higher number of licensed swine operations. We did not observe this in 2008–2009 or 2011–2012, nor did we observe a relationship between ILI onset week and number of swine operations. Conclusions: Our findings suggest that concentrated swine feeding operations amplified transmission of influenza during years in which H1N1 was circulating. This has implications for vaccine strategies targeting swine workers, as well as virologic surveillance in areas with large concentrations of swine.